Psychosocial aspects that influence performance in team sports - Clara Maria Silvestre Monteiro de Freitas; João Manuel Farias; Aloísio Bezerra Sandes Junior; Carlos Augusto Cardoso Kucera; Rebeca Rodrigues Melo; Ana Carolina Carneiro Leão; Ana Elizabeth Vieira da Cunha (Universidade Federal de Santa Catarina, 2009)
The objective of the present investigation was to discuss the psychosocial factors that inhibit or stimulate performance, presenting training suggestions that include interventions to enhance performance. In addition, sports performance was discussed from the perspective of quality of life. A descriptive quantitative-cum-qualitative field method was employed. A total of 103 athletes engaged in team sports from five institutions in the city of Recife, Pernambuco, participated in the study. The WHOQOL, FISSB and FISS-J questionnaires were used. The following results were obtained: "team spirit is extremely important for winning" (98.0%) and "satisfaction in working as a team" (95.0%). With respect to situations that inhibit performance, the most representative findings were "poor refereeing" (81.4%) and "losing a game practically already won" (75.7%). From the quality of life perspective, the main indicators were "my life is meaningful" (92.2%) and "a good quality of life rating" (89.2%). These analytical categories indicate the need for sports training to be carried out from a humanistic standpoint in which the training technology interacts with sociopsychological needs, thus potentiating the physical, technical and tactical qualities of the athletes.